2017
DOI: 10.1097/mol.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, lipids and atherosclerosis

Abstract: Based on available data, adiponectin represents a multifaceted biomarker that may beneficially affect atherosclerosis, inflammation and insulin resistance pathways. However, there are conflicting results with regard to the associations between adiponectin levels and the prevalence and outcomes of cardiometabolic diseases. Further research on the potential clinical implications of adiponectin in the diagnosis and treatment of such diseases is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 132 publications
1
89
0
7
Order By: Relevance
“…After ADP binds to its receptor, the biological effects of ADP on insulin sensitivity seem to be mediated by its ability to activate AMPK, MAPK, and peroxisome proliferator-activated receptors-α signaling pathways, resulting in an increase of fatty acid oxidation and glucose uptake in muscle tissue, as well as an inhibition of gluconeogenesis in the liver [62]. In addition, ADP can also promote the production of endothelial nitric oxide to exert anti-atherosclerotic effects by improving the vascular dysfunction and inhibiting vascular inflammation [64,65]. With the deepening of research, it has been found that osteoblasts can express ADP and its receptors, and it can be concluded that ADP may be a key factor in metabolic bone disease [66].…”
Section: Oc and Exercisementioning
confidence: 99%
“…After ADP binds to its receptor, the biological effects of ADP on insulin sensitivity seem to be mediated by its ability to activate AMPK, MAPK, and peroxisome proliferator-activated receptors-α signaling pathways, resulting in an increase of fatty acid oxidation and glucose uptake in muscle tissue, as well as an inhibition of gluconeogenesis in the liver [62]. In addition, ADP can also promote the production of endothelial nitric oxide to exert anti-atherosclerotic effects by improving the vascular dysfunction and inhibiting vascular inflammation [64,65]. With the deepening of research, it has been found that osteoblasts can express ADP and its receptors, and it can be concluded that ADP may be a key factor in metabolic bone disease [66].…”
Section: Oc and Exercisementioning
confidence: 99%
“…APN is well-known as a mediator in lipid metabolism. It is positively correlated with HDL-C and negatively associated with LDL cholesterol (LDL-C) and triglyceride concentrations (Katsiki et al, 2017). All evidences indicate that APN exerts a multifaceted effect in improving atherosclerosis in brain by regulating atherogenic factors.…”
Section: Atherosclerosismentioning
confidence: 97%
“…Relative to insulin‐resistant obese adolescents, insulin‐sensitive obese adolescents demonstrate higher circulating adiponectin, an anti‐inflammatory adipocytokine . Whilst glucose, insulin, and HbA1c concentrations are important diagnostic biomarkers of T2D, adiponectin, and to a greater extent its high‐molecular‐weight (HMW) oligomeric complex, are also early and sensitive biochemical predictors of future T2D . Indeed, in overweight and obese adolescents, hypoadiponectinemia was demonstrated to precede cardio‐metabolic dysregulation by 6 years .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in overweight and obese adolescents, hypoadiponectinemia was demonstrated to precede cardio‐metabolic dysregulation by 6 years . Furthermore, despite normal fasting glucose and HbA1c levels, obese adolescents with insulin‐resistance as measured by hyperinsulinemic‐euglycemic clamp demonstrated deranged serum adiponectin …”
Section: Introductionmentioning
confidence: 99%